ZakÄt, Regional Autonomy, and Sustainable Development (Review of MaqÄá¹£id al-sharÄ«`ah System Approach) - Zeinal Arifin Haji Munir; Muh. Salahuddin (Jurnal Ilmiah Ekonomi Islam, 2023)
Based on the Maqad al-shar'ah System Approach, this study aims to develop the concepts of zakat, regional autonomy, and sustainable development. Zakat is an adaptable tool for development. Indonesia is a dynamic, space-and-time-interacting society. In the Indonesian context, maqid al-shar'ah is used as an elegant methodological bridge between zakat and development. In terms of regional autonomy, each region can benefit from the economic potential and political policy direction by establishing zakat organisations as intermediaries in the style of a bank.